Pharmacological activities and potential use of bovine colostrum for peptide-based radiopharmaceuticals: A review - Crhisterra Ellen Kusumaningrum; Eva Maria Widyasari; Maula Eka Sriyani; Hendris Wongso (Pharmacia, 2021)
Bovine colostrum (BC) is the initial milk produced by cows after giving birth. It has been used to treat human diseases, such as infections, inflammations, and cancers. Accumulating evidence suggests that bovine lactoferrin and bovine antibodies seem to be the most important bioactive constituents in BC. Thus, BC has also been reviewed for its potential to deliver short-term protection against coronavirus disease 2019 (COVID-19). In addition, it can potentially be explored as a precursor for peptide-based radiopharmaceuticals. To date, several bioactive peptides have been isolated from BC, including casocidin-1, casecidin 15 and 17, isracidin, caseicin A, B, and C. Like other peptides, bioactive peptides derived from BC could be used as a valuable precursor for radiopharmaceuticals either for diagnosis or therapy purposes. This review provides bovine colostrum’s biological activities and a perspective on the potential use of peptides from BC for developing radiopharmaceuticals in nuclear medicine.